The health impact of living in a nursing home with a predominantly different spoken language - Batista, Ricardo; Prud’homme, Denis; Hsu, Amy T.; Guérin, Eva; Bouchard, Louise; Rhodes, Emily; Talarico, Robert; Desaulniers, Jacinthe; Manuel, Douglas; Tanuseputro, Peter (Journal of the American Medical Directors Association, 2019)
Abundant research shows that linguistic barriers can have a negative impact on access to and quality of health care, as well as a patient's health outcomes.1–3 Establishing a culturally appropriate environment, by providing care to nursing home residents in their preferred language, is key in providing good-quality long-term care (LTC) services.4,5 French is one of Canada's 2 official languages. In Ontario, Canada, studies using population-based data have shown that Francophones have a lower perception of good health, higher prevalence of chronic diseases, and greater dependency on LTC services compared to Anglophones.6,7 However, the impact of language discordance on the outcomes of residents in nursing homes has not been previously explored.

L’offre active et l’accessibilité des services sociaux et de santé chez les personnes atteintes de démence en contexte francophone minoritaire - Bélair, Josée (Université d'Ottawa, 2019)
À l’heure actuelle, les besoins de soins de santé augmentent en réponse à la démographie vieillissante (Organisation mondiale de la santé, 2018). Pourtant, la difficulté d’accès aux services sociaux et de santé chez les usagers en situation minoritaire est une réalité présentée à l’aide de la littérature scientifique. En ce qui a trait aux populations minoritaires de la ville d’Ottawa, les études antérieures permettent de démontrer les obstacles touchant plus particulièrement les personnes francophones dans l’accessibilité des services sociaux et de santé (Kubina et collab., 2018). Dans le contexte de cette étude qualitative, le diagnostic de démence est pris en compte en tant que facteur explicatif de la difficulté accrue vécue chez les aînés francophones dans le recours aux services sociaux et de santé (Carbonneau et Drolet, 2014b). Un total de cinq proches aidants de la ville d’Ottawa a été recruté dans le but d’alimenter les objectifs de la recherche, c’est-à-dire : 1) d’identifier les barrières linguistiques dans la trajectoire des services sociaux et de santé ; 2) d’identifier l’influence des structures du Cadre d’analyse des leviers d’action pour l’accès et l’intégration des services sociaux et de santé pour les communautés de langue officielle en situation minoritaire (CALA) (Savard et collab., 2017) (Voir figure 1) dans l’accès aux services sociaux et de santé chez la population à l’étude. Quoique la majorité des participants à la recherche aient exprimé leur satisfaction par rapport aux services en français reçus pour leur proche atteint d’une démence, certaines barrières linguistiques telles que le manque de continuité dans les services en français ont été identifiées ainsi que le manque d’information quant à la disponibilité des services dans la communauté. De plus, la majorité des participants à la recherche ont pu identifier au moins un moment où les services à leur disponibilité étaient strictement en anglais. Bref, parmi les cinq proches aidants interviewés, quatre ont mentionné la nécessité de lutter pour l’obtention des services en français.

La santé mentale des francophones en situation minoritaire au Canada : un portrait tiré de l’Enquête sur la santé dans les collectivités canadiennes-Santé mentale 2012 - Bouchard, Louise; Colman, Ian; Dubois, Alejandra; Sucha, Ewa (Université d’Ottawa et Institut du Savoir Montfort, 2019)
fs-ref-orig: Bouchard, L., Colman, I., Dubois, A. et Sucha, E. (2019). La santé mentale des francophones en situation minoritaire au Canada : un portrait tiré de l’Enquête sur la santé dans les collectivités canadiennes-Santé mentale 2012. Université d’Ottawa et Institut du Savoir Montfort. fs-code-orig: Bouchard-2019a

The mental health of Francophone minorities: An overview from the Canadian community health survey-Mental health 2012 - Bouchard, Louise; Colman, Ian; Dubois, Alejandra; Sucha, Ewa (University of Ottawa & Institut du Savoir Montfort, 2019)
fs-ref-orig: Bouchard, L., Colman, I., Dubois, A., & Sucha, E. (2019). The mental health of Francophone minorities: An overview from the Canadian community health survey-Mental health 2012. University of Ottawa & Institut du Savoir Montfort. fs-code-orig: Bouchard-2019e

Profil santé mentale des communautés francophones en situation minoritaire au Canada. Rapport abrégé - Bouchard, Louise; Dubois, Alejandra; Sucha, Ewa; Colman, Ian (Université d'Ottawa et Institut du Savoir Montfort, 2019)

Vivre et travailler en français à Iqaluit (Nunavut) : regards de professionnels de la santé sur le capital social de la communauté francophone - Charrier, Marie-Josée (Revue du Nouvel-Ontario, 2019)

La pénurie de professeures de sciences infirmières au Canada et ses effets sur les programmes de formation en sciences infirmières offerts en français - Chartrand, Julie; Vandyk, Amanda; Beké, Émilie; Balasa, Rebecca; Loranger, Catherine; Muray, Mwali; Chartrand, Mariève; Baker, Cynthia (Minorités linguistiques et société, 2019)
Cette étude qualitative décrit la pénurie de professeures en sciences infirmières et ses effets actuels et potentiels sur les programmes canadiens de formation en sciences infirmières offerts en français, ainsi que les stratégies préconisées par les directrices de ces programmes afin d’en atténuer les effets. Les effets de la pénurie sont particulièrement préoccupants dans le cas des programmes offerts dans un contexte francophone minoritaire ou en région éloignée. La pénurie mettrait en péril les programmes offerts en français et menacerait, par le fait même, la qualité des services de santé offerts aux communautés francophones minoritaires au Canada. Mots-clés : pénurie professorale, sciences infirmières, professionnels de la santé, services et soins de santé en français, communautés francophones en situation minoritaire

L’offre active une culture de respect, une culture d’excellence : dépliant [infographie] - Commissariat aux langues officielles (2019)
fs-ref-orig: Commissariat aux langues officielles. (2019). L’offre active une culture de respect, une culture d’excellence : dépliant [infographie]. fs-code-orig: Commissariat aux langues officielles-2019

Promoting the health and well-being of English-speaking Seniors in Quebec. A community model (infographic) - Community Health And Social Services Network/Réseau communautaire de santé et de services sociaux (2019)
fs-ref-orig: Community Health And Social Services Network. (2019). Promoting the health and well-being of English-speaking Seniors in Quebec. A community model [infographic]. fs-code-orig: Community Health And Social Services Network-2019

Access to resources in the community through navigation: Protocol for a mixed-methods feasibility study - Dahrouge, Simone; Gauthier, Alain; Chiocchio, François; Presseau, Justin; Kendall, Claire; Lemonde, M.; Chomienne, Marie-Hélène; Perna, A.; Toal-Sullivan, Darene; Devlin, R. A.; Timony, Patrick; Prud'homme, Denis (JMIR Publications, 2019)
Background: Community-based health and social resources can help individuals with complex health and social needs achieve their health goals. However, there is often inadequate access to these resources due to a lack of physician and patient awareness of available resources and the presence of social barriers that limit an individual’s ability to reach these services. Navigation services, where a person is tasked with helping connect patients to community resources, embedded within primary care may facilitate access and strengthen the continuity of care for patients. Objective: This study aims to describe the protocol to assess whether the implementation of the Access to Resources in the Community (ARC) navigation model (an innovative approach to navigation services) is feasible, including its potential to achieve its intended outcomes, and to assess the viability of the evaluation approach. Methods: The study consists of a single-arm, prospective, explanatory, mixed-methods, pre-post design feasibility study focusing on primary care practice settings with vulnerable populations. Participants include primary care providers and patients. Results: Enrollment is closed with 82 patients. Navigation services have ended for 69 patients. Conclusions: The study of an innovative complex intervention requires an adequate assessment of the feasibility of the intended approach during which the potential challenges of the planned intervention and need for its adaptation may be uncovered. Undertaking a feasibility study of the ARC navigation model from a conceptually clear and methodologically solid protocol will inform on the practicality and acceptability of the approach, demand for the services, ease of implementation, quality of integration of the new services within primary care, and practicality and potential for efficacy prior to initiating a randomized controlled trial.

Impact of language barriers on quality of care and patient safety for official language minority Francophones in Canada - de Moissac, Danielle; Bowen, Sarah (Journal of Patient Experience, 2019)
Introduction: The risks to patient safety and quality of care faced by members of linguistic minority groups have been well-documented. However, little research has focused on the experience of official language minorities in Canada. Methods: This multiple method study (online and paper-based surveys combined with semi-structured individual interviews with patients and interpreters-health navigators) explored the experience of minority Francophones living in 4 Canadian provinces. Results: Patients and interpreters-navigators described experiences where language barriers contributed to poorer patient assessment, misdiagnosis and/or delayed treatment, incomplete understanding of patient condition and prescribed treatment, and impaired confidence in services received. Reliance on Google Translate and ad hoc, untrained interpreters are commonly reported, in spite of evidence highlighting the risks associated with such practice. Conclusion: Increased awareness that the risks of language barriers apply to official language minorities is essential.

Barriers to HIV care among Francophone African, Caribbean and Black immigrant people living with HIV in Canada: A protocol for a scoping systematic review - Djiadeu, Pascal; Nguemo, Joseph; Mukandoli, Chantal; Odhiambo, Apondi. J.; Lightfoot, David; Mbuagbaw, Lawrence; Nelson, LaRon. E. (BMJ Open, 2019)
Introduction Language is a social determinant of health. Addressing social determinants of health is paramount to successful progression along the HIV-care continuum. Canada is a bilingual country with French and English as official languages. There are few studies to date that have focused on the impact of being a French-speaking linguistic minority on the HIV-care continuum. The primary objective of this scoping, systematic review of literature is to evaluate existing gaps in access to HIV- care among French-speaking people living with HIV in Canada. Our primary outcome is healthcare services availability and access for French- speaking people living with HIV. Methods and analyses Our scoping, systematic review will draw on a systematic search of published literature, both quantitative and qualitative studies published on French-speaking individuals' healthcare and HIV status in Canada, with particular emphasis on the province of Ontario. We will conduct our search in MEDLINE, the Excerpta Medica Database, the Cumulative Index to Nursing and Allied Health Literature, Web of Science, EBSCO and Google Scholar for work published between 1990 and 2018. Identified articles will be screened in duplicate and full-text articles of relevant studies will be retrieved. Data will also be extracted by two researchers working independently. Any discrepancies that arise will be resolved by consensus or by consulting a third author. Our findings will be reported according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses. Ethics and dissemination Our proposed research will not be conducted with human participants. We will only use secondary published data and therefore ethics approval is not required. Our findings will be disseminated as peer reviewed manuscripts at conferences and student rounds, and could be of interest to government health agencies and local HIV/AIDS service organisations.

Comprendre l’expérience des femmes âgées en matière de l’accessibilité aux services sociaux et de santé en contexte francophone minoritaire [mémoire de maîtrise, Université d'Ottawa] - Dubuc, Vanessa (Université d'Ottawa, 2019)
Au Canada, les francophones en contexte minoritaire demeurent contraints au niveau de l’accès aux services sociaux et de santé en français en raison de barrières linguistiques. De plus, les femmes âgées en contexte francophone minoritaire sont sujettes aux inégalités vécues par les femmes âgées de façon générale, mais subissent également de la discrimination liée à leur statut de minorité. La présente recherche s’intéresse à l’expérience des femmes âgées en contexte francophone minoritaire en matière d’accessibilité aux services sociaux et de santé. De manière plus précise, cette recherche a pour but : 1) d’identifier les facilitateurs et les défis rencontrés par ces femmes ; 2) de comprendre la manière dont ces facilitateurs et ces défis ont des effets sur les différentes sphères de leur vie ; 3) examiner l’effet des structures institutionnelles et organisationnelles quant à l’accessibilité aux services sociaux et de santé de celles-ci. Afin de recueillir nos données, des entrevues semi-structurées ont été effectuées auprès de quatre participantes. L’analyse thématique des données, suivant un cadre théorique féministe intersectionnel, permet de mettre en évidence les éléments suivants selon les expériences des participantes : 1) l’accès aux services sociaux et de santé en contexte francophone minoritaire ; 2) la question du genre ; et 3) les réalités structurelles. Concrètement, les résultats indiquent que les participantes ont de la difficulté à accéder à des services sociaux et de santé dans leur langue, mais que le fait de s’identifier comme une femme ne semble pas jouer un rôle déterminant dans leur accès aux services en français. À la lumière des résultats, des recommandations sont proposées afin de mieux répondre aux besoins des groupes en situation linguistique minoritaire. Mots clés : francophone minoritaire, femme âgée, accès aux services sociaux et de santé, féminisme intersectionnel

Leçons apprises sur la navigation des services de santé en français - Entité de planification des services de santé en français pour les régions de Waterloo, Hamilton, Niagara, Haldimand, Brant, Wellington (2019)
fs-ref-orig: Entité de planification des services de santé en français pour les régions de Waterloo, Wellington, Hamilton, Niagara, Haldimand, Brant. (2019). Leçons apprises sur la navigation des services de santé en français. fs-code-orig: Entité de planification des services de santé en français pour les régions de Waterloo, Wellington, Hamilton, Niagaram Haldminand, Brant-2019

Évaluation des besoins des francophones et des Acadiens de la région de Saint-Jean pour un service de navigation - Forest, Mariève (Réseau santé en français de Terre-Neuve-et-Labrador, 2019)

Promoting the health and well-being of English-speaking seniors in Quebec. A community model - Kueber, Rusell (Community Health and Social Services Network, 2019)

Promotion de la santé et du bien-être des aînés d’expression anglaise du Québec : un modèle communautaire - Kueber, Russell (Réseau communautaire de santé et de services sociaux, 2019)

Actes du colloque : l'offre active des services sociaux et de santé en français - La Cité universitaire francophone, Université de Régina; Consortium national de formation en santé (2019)

Language and culture in the caregiving of people with dementia in care homes - What are the implications for well-being? A scoping review with a Welsh perspective - Martin, Conor; Woods, Bob; Williams, Siôn (Journal of Cross-Cultural Gerontology, 2019)
The loss of language skills is one of the most challenging aspects of living with dementia. This is particularly true for bilingual individuals, who have difficulty in maintaining fluency in more than one language. Language and culture overlap greatly, with potential implications for the well-being of people with dementia (PWD) being cared for in their ‘second’ language or culture. Our aim was to review the available relevant literature, together with an examination of the potential effects of linguistic incongruity on healthcare in general for Welsh speakers in Wales. A literature search yielded 50 articles, which were analysed using the scoping review methodological framework. We found that the presence of cultural and linguistic congruity was beneficial for PWD living in care homes, and that their absence was detrimental. The absence of linguistic congruity is a strong predictor for decreased well-being in people in such settings, due to communication barriers between residents and carers, which result mainly from the loss of PWD’s second language skills. Such barriers may lead to inappropriate care, e.g. being unable to obtain help to self-care, as well as social isolation. This review suggests that strategies need to be developed across the world to accommodate bilingual individuals requiring a care home for their dementia needs. There is a particular dearth of research regarding the influence of bilingualism on the experience of dementia care in those areas of the UK where the indigenous population are most likely to be bilingual (i.e. parts of Wales).

Social service accessibility in Montreal’s English-speaking disability community: A needs-based assessment - Nash, Aubrey (McGill University, 2019)
Health and social service systems can be difficult to traverse, especially in the stressful situations that often necessitate accessing them. In Quebec, these difficulties are exacerbated for English speaking or limited French-proficient persons. This thesis employs a needs-based assessment to explore how linguistic-based access barriers to health and social services affect Montreal’s English-speaking Disability community, focusing on those with intellectual and/or developmental disabilities and their caregivers/advocates. It identifies the community’s needs and proposes three key issues that result in the needs being unmet by the social service system. Specifically, the issues are (i) inaccessible information for limited French-proficient persons, as many important documents are available in only French; (ii) the primary method for bolstering language congruency between service users and providers relies on the service seeker to acquire French, which is incompatible with the lived experiences of many members of the Disability community; (iii) limited options for English services across Montreal. This thesis indicates the protection of the French language under the Charter of the French Language (1977) impacts the ability of the Act Respecting Health Services and Social Services (1991) to protect the rights of English-speaking Quebeckers to receive services in English. Through a human rights model of Disability and citizenship lens, it suggests that language laws can be understood and implemented to protect the Quebecois identity while ensuring active inclusion of otherwise marginalized communities in health and social service systems

L’offre active de services en français : généalogie d’un outil de politique publique - Normand, Martin (Francophonies d'Amérique, 2019)
L’offre active de services en français est un principe qui s’est rapidement imposé dans le discours des principaux intervenants dans le domaine de la promotion et de la protection des langues officielles et de la dualité linguistique au Canada. Elle a été intégrée à des politiques, à des règlements et à des lois au palier fédéral et dans plusieurs provinces canadiennes. Plusieurs travaux ont été consacrés aux aspects liés à la mise en oeuvre du principe. Cet article va au-delà de ces contributions pour retracer l’histoire de l’offre active. Il répond à deux questions : 1) quelle est l’origine de l’offre active ? et 2) quels sont les principaux jalons dans son évolution et sa diffusion ? L’hypothèse est que les représentations initiales de l’offre active n’étaient pas que techniques ou formalistes et qu’elles se sont effritées avec le temps. La recherche repose essentiellement sur des sources primaires et secondaires, qui nous ont permis de reculer jusqu’au moment où le principe semble avoir émergé. Le texte s’organise autour de trois périodes : la conceptualisation, l’institutionnalisation et la diffusion de l’offre active.

Étude de besoins sur les services de santé mentale en français. Rapport final - PGF Consultants (Société Santé en français et Santé Canada, 2019)
fs-ref-orig: PGF Consultants. (2019). Étude de besoins sur les services de santé mentale en français. Rapport final. Société Santé en français et Santé Canada. fs-code-orig: PGF Consultants-2019

Promotion de la santé et du bien-être des aînés d'expression anglaise du Québec. Un modèle communautaire( infographie) - Réseau communautaire de santé et de services sociaux/Community Health and Social Services Network (2019)
fs-ref-orig: Réseau communautaire de santé et de services sociaux. (2019). Promotion de la santé et du bien-être des aînés d'expression anglaise du Québec. Un modèle communautaire [infographie]. fs-code-orig: Réseau communautaire de santé et de services sociaux-2019

Affichage de postes bilingues dans la région de Kingston. Un guide utile pour les employeurs des secteurs de la santé et des services sociaux et communautaires | Job posting resource for bilingual positions in the Kingston area. A useful guide for employers in the healthcare and social community services sectors - Réseau des services de santé en français de l'Est de l'Ontario (A useful guide for employers in the healthcare and social community services sectors, 2019)

Évaluation des services communautaires pour les aînées et aînés d’expression anglaise de Gaspésie-îles-de-la-Madeleine - Richardson, Mary (2019)
fs-ref-orig: Richardson, M. (2019). Évaluation des services communautaires pour les aînées et aînés d’expression anglaise de Gaspésie-îles-de-la-Madeleine. fs-code-orig: Richardson-2019

Pratique # 1 : Le Guide de mise en œuvre du mandat linguistique d’Actionmarguerite (Manitoba). - Savard, Jacinthe; Savard, Sébastien; van Kemenade, Solange; Benoît, Josée; Buhay, Corrina; Youbi, Sara; Kubina, Lucy-Ann (2019)

Pratique # 15 : Le volet « santé et services sociaux » de l’Association des Townshippers (Québec) - Savard, Jacinthe; Savard, Sébastien; van Kemenade, Solange; Benoît, Josée; Buhay, Corrina; Youbi, Sara; Kubina, Lucy-Ann (2019)

Pratique # 2 : Une maisonnée francophone au Foyer Summerset (Île-du- Prince-Édouard) - Savard, Jacinthe; Savard, Sébastien; van Kemenade, Solange; Benoît, Josée; Buhay, Corrina; Youbi, Sara; Kubina, Lucy-Ann (2019)
fs-ref-orig: Savard, J., Savard, S., Van Kemenade, S., Benoît, J., Buhay, C., Youbi, S., et Kubina, L.A. (2019). Pratique # 2 : Une maisonnée francophone au Foyer Summerset (Île-du- Prince-Édouard). Dans : GReFoPS. Répertoire de pratiques novatrices en santé et service social en langue officielle en contexte minoritaire. https://www.grefops.ca/repertoire_pratiques_novatrices.html fs-code-orig: Savard-2019a

Pratique # 8 : Une infirmière coordonnatrice bilingue en milieu hospitalier à Halifax (IWK Health) (Nouvelle-Écosse) - Savard, Jacinthe; Savard, Sébastien; van Kemenade, Solange; Benoît, Josée; Buhay, Corrina; Youbi, Sara; Kubina, Lucy-Ann (2019)
fs-ref-orig: Savard, J., Savard, S., van Kemenade, S., Benoît, J., Buhay, C., Youbi, S., et Kubina, L.A. (2019, mise à jour 2025). Pratique # 8 : Une infirmière coordonnatrice bilingue en milieu hospitalier à Halifax (IWK Health) (Nouvelle-Écosse). Dans : GReFoPS. Répertoire de pratiques novatrices en santé et service social en langue officielle en contexte minoritaire. https://www.grefops.ca/repertoire_pratiques_novatrices.html fs-code-orig: Savard-2025f

Pratique # 9 : Les Soins primaires communautaires pour aînés (Primary Care Outreach to Seniors) (Ontario) - Savard, Jacinthe; Savard, Sébastien; van Kemenade, Solange; Benoît, Josée; Buhay, Corrina; Youbi, Sara; Kubina, Lucy-Ann (2019)
fs-ref-orig: Savard, J., Savard, S., Van Kemenade, S., Benoît, J., Buhay, C., Youbi, S., et Kubina, L.A. (2019). Pratique # 9 : Les Soins primaires communautaires pour aînés (Primary Care Outreach to Seniors) (Ontario). Dans : GReFoPS. Répertoire de pratiques novatrices en santé et service social en langue officielle en contexte minoritaire. https://www.grefops.ca/cahier_de_pratiques.html fs-code-orig: Savard-2019c

Des soins de santé et des services sociaux sécuritaires dans sa langue. Réponse au projet de Cadre canadien sur la qualité des soins et la sécurité des patients - Société Santé en français (2019)
fs-ref-orig: Société Santé en français. (2019). Des soins de santé et des services sociaux sécuritaires dans sa langue. Réponse au projet de Cadre canadien sur la qualité des soins et la sécurité des patients. fs-code-orig: Société Santé en français-2019

Services de santé mentale et de dépendances à Terre-Neuve-et-Labrador. Les besoins des francophones et des Acadiens dans cinq communautés de la province - van Kemenade, Solange; Forest, Mariève (Sociopol, 2019)
fs-ref-orig: van Kemenade, S. et Forest, M. (2019). Services de santé mentale et de dépendances à Terre-Neuve-et-Labrador. Les besoins des francophones et des Acadiens dans cinq communautés de la province. Rapport soumis au Réseau Santé en français de Terre-Neuve-et-Labrador. Sociopol. fs-code-orig: van Kemenade-2019

Services de santé mentale et de dépendances à Terre-Neuve-et-Labrador. Les besoins des francophones et des Acadiens dans cinq communautés de la province (Sommaire) - van Kemenade, Solange; Forest, Mariève (Sociopol, 2019)
fs-ref-orig: van Kemenade, S. et Forest, M. (2019). Services de santé mentale et de dépendances à Terre-Neuve-et-Labrador. Les besoins des francophones et des Acadiens dans cinq communautés de la province (Sommaire). Rapport soumis au Réseau Santé en français de Terre-Neuve-et-Labrador. Sociopol. fs-code-orig: van Kemenade-2019b

The Needs of Francophones and Acadians in Five Communities in the Province (Summary Report). - van Kemenade, Solange; Forest, Mariève (Sociopol, 2019)
fs-ref-orig: van Kemenade, S. et Forest, M. (2019). The Needs of Francophones and Acadians in Five Communities in the Province (Summary Report). Submitted to the Réseau Santé en français de Terre-Neuve-et-Labrador. Sociopol. fs-code-orig: van Kemenade-2019c